Antihemophilic Factor: Separation of an Active Fragment Following Dissociation by Salts or Detergents - Owen, W. G; Wagner, Robert H. (Thrombosis and Haemostasis, 1972)
Dissociation of canine antihemophilic factor (factor VIII, molecular weight >2 × 106) by salts and detergents was studied with the use of agarose gel chromatography. The dissociated fragments retained antihemophilic factor activity. Partial dissociation occurred in 1 M or 2 M KCl, 1 M KBr, 0.25% sodium desoxycholate and 0.1% Triton X-100, but essentially no dissociation was observed in 3 M KC1. A high degree of dissociation occurred in 0.25 M CaCl2. Removal of Ca2+ before chromatographic fractionation of the preparation resulted in complete reversal of the dissociation. However, upon separation of an active, dissociated fraction from the very high molecular weight components by gel chromatography in 0.25 M CaCl2, followed by removal of Ca2+ from the fraction, no tendency toward reaggregation was seen. The apparent molecular weight of the dissociated fragment, determined by gel chromatography, is about 25,000. It is proposed that antihemophilic factor activity is associated with a molecule, of relatively low molecular weight, which in plasma or partially purified fractions is bound by electrostatic and hydrophobic bonds to a high molecular weight carrier. The activities of both dissociated and undissociated preparations were neutralized by an antibody to human antihemophilic factor. In contrast to the behavior of undissociated antihemophilic factor, the activity of the dissociated preparation was not affected by incubation with a dilute, highly purified thrombin preparation.